An Aflatoxin-M1 biochip using graphene quantum dot-gold hybrid nanoparticles. (1st March 2023) - Ramalingam, Saipriya; Elsayed, Abdallah; Singh, Ashutosh
Graphical abstract: Highlights: Quick microwave assisted synthesis of Graphene-Au quantum dots. Microfluidic biochip to detect trace AF-M1 in the pM range. Portable system with a 20-minute assay time. Spiked milk sample was used to validate sensor performance. Abstract: Toxicosis through food and feed has remained a point of concern to food sectors across the globe. Although strict regulations have been implemented in developed and developing countries, their detection in food matrices is an evolving science. This study focuses on the development and fabrication of an electrochemical microfluidic biosensor that deploys aptamers to detect trace concentrations of Aflatoxin-M1 (AF-M1) in milk samples. The use of graphene quantum dot composite with Au nanoparticles anchors the aptamer to the sensor surface and improves its signal conductivity. The screen-printed carbon electrode modified with graphene quantum dot-gold nanoparticles is placed between two polydimethylsiloxane layers to promote portability and improve mixing effects. Differential pulse voltammograms indicated that the linear range of the sensor was between 100 pM and 2 nM making the limit of detection 0.3 nM. Interfering molecules of similar size were analyzed, to evaluate sensor selectivity.